THE STUDY OF MISREPRESENTED HADITHS ON THE INTERNET ABOUT MUSLIM AND NON-MUSLIM RELATIONSHIPS - Haq, Ahmad Yusronil (Nabawi: Journal of Hadith Studies, 2023)
Relations between Muslims and Non-Muslims are often tinged with negative issues for various reasons and in various aspects. And this understanding circulates on the internet network which is easily accessible by the public, such as al-ahkam.net, markazsunnah.com, dan nisa-assunnah.com. But his explanation contradicts the meaning of the Qur'an and authentic Hadith. This research will discuss three hadiths about the relationship between Muslims and non-Muslims that are misunderstood in that three internet networks. The data are read according to hadith science standards which include assessing the quality of hadith, understanding the content of hadith through the fiqh al-hadith approach from the perspective of Yusuf al-Qaradawi, Muhammad al-Ghazali, and Ali Mustafa Yaqub, and supported by the views of other ulama regarding this discussion. This research shows that: (1) Hadith "I was ordered to fight Non-Muslims until he converted to Islam" was an order to fight the polytheists of the Arabian Peninsula who at that time were fighting the Muslims, (2) Hadith "Who imitates a people, then he is part of them" was prohibition of resembling non-Muslims in matters related to al-'Ibadah al-Mahdhah, not in al-'Ibadah ghairu al-Mahdhah as long as the substance does not contradict with Islamic values, (3) Hadith "I get rid of every muslim who lives in the midst of musyriks" was the words of the Prophet to those who are obliged to do jihad, but they do not participate in jihad, and instead they live in the midst of polytheists who are fighting Islam. [Hubungan Muslim dengan Non-Muslim kerap diwarnai dengan isu-isu negatif, banyak yang berpandangan dengan salah satu aspek dalil Al-Qur’an atau Hadis bahwa tidak boleh Muslim berinteraksi dengan non-Muslim dengan berbagai alasan. Dan pemahaman ini ternyata beredar di jaringan internet yang sangat mudah diakses oleh masyarakat. Namun penjelasannya bertentangan dengan makna Al-Qur’an dan Hadis yang lebih shahih. Penelitian ini menunjukkan bahwa: (1) Hadis “Aku Diperintah untuk Memerangi Non-Muslim sampai Ia Masuk Islam” ini maknanya tidak seperti dugaan sementara orang bahwa Nabi diperintahkan untuk membunuh siapapun manusia yang tidak percaya kepada Allah dan Rasul-Nya, melainkan sasaran kata Non-Muslim disini adalah kaum musyrik yang memerangi kaum Muslim dan yang ketika itu bermukim di Jazirah Arab. (2) Hadis “Siapa yang Menyerupai Suatu Kaum, Maka Ia Termasuk Bagian dari Mereka” ini maknanya tidak seperti dugaan sementara orang bahwa segala amal perbuatan yang menyerupai Non-Muslim hukumnya terlarang, melainkan larangan menyerupai Non-Muslim dalam hadis di atas adalah dalam hal-hal yang berkaitan dengan al-‘Ibadah al-Mahdhah, bukan dalam al-‘Ibadah ghairu al-Mahdhah selama substansinya tidak bertentangan dengan nilai-nilai Islam. (3) Hadis “Aku Berlepas Tangan dari Setiap Muslim yang Berdiam di Tengah-tengah Kaum Musyrik” ini makanannya bukan seperti dugaan sementara orang bahwa Hadis ini menunjukkan larangan untuk berdiam atau bertempat tinggal di negeri-negeri yang secara umum dihuni oleh Non-Muslim, dengan mempertimbangkan sebab hadis ini diucapkan, yakni ada kewajiban berjihad, dan orang-orang tersebut tidak ikut berjihad, dan justru mereka berdiam diri atau tinggal di tengah-tengah kaum musyrik yang sedang memerangi Islam, maka Nabi Muhammad Saw. tidak bertanggungjawab atas orang tersebut apabila ia terbunuh.]